Edukasi Lingkungan serta Pelestarian Budaya Lokal: Implementasi Pemberian Maggot dan Kegiatan Menghias Bokor sebagai Aksi Sosial Ekonomi Berbasis Komunitas - Ni Kadek Sri Martini; Amanda Putri Ayu; Faizal Akbar Gafur; Putu Harry Hadi Putra (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Socio-economic action activities aim to increase participants' awareness of the importance of social and environmental roles through educational and participatory approaches. This study aims to describe the implementation of the activity of feeding maggot to chickens as a form of organic waste utilization and the activity of decorating bokor as a preservation of local culture. The method used was participatory observation, where participants were directly involved in both activities. The results showed that participants understood the benefits of maggot as a waste management solution and alternative feed, and showed high enthusiasm in decorating bokor as a form of preserving cultural values. This activity was able to increase social, environmental, and cultural awareness in participants in an integrated manner in one series of activities.